What does Truth and Reconciliation teach us about degrowth in settler societies? An exploration of the interconnections between degrowth and the TRC calls to action - Gingrich, Kelly; Howarth, Elaine; Stratton, Anna; Shafazand, Shahed (2023)
Degrowth offers pathways to stay within ecological limits while increasing human and planetary wellbeing. As settler scholars living in so-called Canada, we see a gap in the degrowth branch of ecological economics regarding degrowth transitions within settler societies, as much of this literature comes out of a European context. In this paper, we attempt to analyze the Calls to Action from the Truth and Reconciliation Commission of Canada (TRC) and the United Nations Declaration on the Rights of Indigenous Peoples, to explore how a degrowth transition may help us move forward together on the path to Reconciliation with (and decolonization of) First Nations, Metis and Inuit Peoples. We do this by reviewing relevant academic and grey literature, showing the interconnections between degrowth’s emphasis on ecological limits and reconciliation with the Land; on autonomy and Indigenous sovereignty; and on moving towards a multiplicity of knowledges to live ‘the good life’. Here, we offer an exploration of these interconnections to open up three lines of inquiry. We explore how we might ground degrowth transitions in reconciliation with Indigenous Peoples and the Land, question what degrowth means on occupied Land, and move towards pluralistic and decolonial degrowth imaginaries. We put forward this contribution to the ecological economics and degrowth communities as a challenge to engage with and act upon the Calls to Action from the TRC, and their implications for degrowth.